A multi-proxy lacustrine record of last deglacial–early Holocene environmental variability in the lower Yangtze region from the Chaohu Lake Basin, eastern China. Issue 3 (30th August 2017) - Guan, Houchun; Wu, Li; Zhang, Jinzhe; Shen, Shihao; Chu, Dongru; Li, Linying
Abstract: The Rb, Sr, and Ti content, Rb/Sr ratio, grain size, magnetic susceptibility, and magnetic fabric in sediments of the BZK1 core were utilized to reconstruct the evolution of the climatic environment in the Chaohu Lake Basin between the last deglacial and the early Holocene. Multi-proxy analyses indicate that lacustrine sediments in Chaohu Lake clearly record the Bølling-Allerød interstadial, the Younger Dryas event and dry-cold climate events occurring between 10.7 cal ka BP and 10.5 cal ka BP. At approximately 15.6–14.8 cal ka BP, the waters became deeper and the climate turned cool. The climate subsequently shifted to a relatively humid period and the lake was largest from 14.8 to 12.8 cal ka BP. From 12.8 to 11.7 cal ka BP, the climate abruptly turned dry and cold and the lake shrank to its lowest level. During 11.7–10.7 cal ka BP, the climate became relatively humid but, from approximately 10.7 to 10.5 cal ka BP, suddenly reverted to a dry and cold state. These climatic change records suggest that lacustrine sediments from the Chaohu Lake Basin in the lower Yangtze region responded actively to global climate changes, comparable with the environmental records from stalagmites and other lacustrine sediments in the region.